2015
DOI: 10.1016/j.str.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of CCDC104/BARTL1 with Arl3 and Implications for Ciliary Function

Abstract: SummaryCilia are small antenna-like cellular protrusions critical for many developmental signaling pathways. The ciliary protein Arl3 has been shown to act as a specific release factor for myristoylated and farnesylated ciliary cargo molecules by binding to the effectors Unc119 and PDE6δ. Here we describe a newly identified Arl3 binding partner, CCDC104/CFAP36. Biochemical and structural analyses reveal that the protein contains a BART-like domain and is called BARTL1. It recognizes an LLxILxxL motif at the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 81%
See 1 more Smart Citation
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 81%
“…The N-termini of Arfrelated GTPases vary in length, sequence and post-translational modifications, and there is therefore ample reasons to believe that they are displaced in different ways to release autoinhibition. For instance, the N-terminus of Arl3-GTP interacts with another protein, 77,78,82 and it is conceivable that there exists Arf-like GTPases in which autoinhibition release involves interactions of the Nterminus with both a protein and a membrane. Understanding this process will be a major theme for future investigations of the molecular mechanisms that regulate the activity of Arf-like GTPases.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%
“…6,7 A homolog of BART, originally identified as CCDC104 (coiled-coiled domain containing 104), now called BARTL1, is much longer than BART but has a domain very similar to the latter. 8 Both BART and BARTL1 bind to the switch regions and also to the amphiphatic helix of the proteins in a similar way. 8,9 The second type of effectors (type2) which bind to both Arl2 and Arl3 are the carrier proteins PDE6d 10 and HRG4/Unc119a 11 and Unc119b.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
“…8 Both BART and BARTL1 bind to the switch regions and also to the amphiphatic helix of the proteins in a similar way. 8,9 The second type of effectors (type2) which bind to both Arl2 and Arl3 are the carrier proteins PDE6d 10 and HRG4/Unc119a 11 and Unc119b. 12 These proteins have a b-sandwich fold and bind only to the switch regions of Arl2 and Arl3.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
See 1 more Smart Citation